Aorto-esophageal fistula: successful open surgical management of two cases. Issue 6 (17th June 2020) - Pahwa, Siddharth; Bhattacharya, Susmit; Mukhopadhyay, Siddhartha; Verma, Ashok
Abstract: An aorto-esophageal fistula (AEF) is a rare yet life-threatening cause of upper gastrointestinal bleeding. We report our experience with open surgical management of two cases of AEF. Both cases presented with almost identical presentations: hematemesis and hemodynamic instability. The aorta in the first patient was normal; the defect was small and was repaired with a Dacron patch. The second patient had an aneurysmal aorta, which was replaced with a Dacron graft. Both cases were performed under partial bypass. The esophageal rent in both patients was debrided, primarily closed and buttressed with a vascularized intercostal pedicle. Nonavailability of endovascular personnel and equipment along with hemodynamic instability of the patient influenced our surgical strategy. Long-term follow-up of these patients is necessary to analyze the outcomes of our surgical repair.